FERGHANA LINGUISTIC SCHOOL (Scientific journal of the Fergana State University, 2023)
The article examines the formation of the linguistic school, which is an integral part of the Fergana philological school, as well as significant work has been done in the past, especially in the years of independence, and shows significant results achieved in the preparation of scientific and pedagogical personnel.